Genetic Variant of Vascular Endothelial Growth Factor (VEGF)-A rs699947 is Associated with Preeclampsia - Anggelia Puspasari; Rina Nofri Enis; Herlambang Herlambang (Cell and BioPharmaceutical Institute, 2022)
Background: Preeclampsia remains as the leading cause of maternal-neonatal mortality and morbidity worldwide. Vascular endothelial growth factor A (VEGF-A) is a proangiogenic factor related to endothelial dysfunction and plays an important role in the preeclampsia pathophysiology. Genetic variants of VEGF-A are associated with VEGF-A expression and preeclampsia risk, however there are still inconsistent results between different populations. The aim of this study was to determine the association of this genetic variant as preeclampsia risk factor.Materials and methods: A cross-sectional study was performed with 76 pregnant women (29 preeclampsia and 47 normotensive) Jambi-Malay ethnic subjects. Sample DNA was extracted from subject’s blood. To determine the genotype, one-step tetra amplification refractory mutation system (ARMS) polymerase chain reaction (PCR) method for VEGF-A rs699947 C/A was used.Results: We found that pregnant woman with AC genotype (p-value=0.045; OR=2.76 ; 95% CI=1.01-7.58) and AA genotype (p-value=0.026; OR=12.44; 95% CI=1.23-126.18) had higher risk of preeclampsia than the CC genotype.Conclusion: Genetic variant VEGF-A rs699947 C/A is associated with preeclampsia. The AC and AA genotype is the risk genotype for preeclampsia in Jambi-Malay ethnics.Keywords: preeclampsia, VEGF-A, genetic variant, Jambi-Malay, Indonesia